1876 Ala. Code 883 - (:unkn) unknown (My University, 1868)
§ 4111: Prohibited the carrying of any rifle or " shot -gun walking cane." Punishable by fine of $500-1000 and imprisonment of no less than 2 years.
Keywords: CARRY